Results of pterygium excision adjunct with conjunctival autograft transplantation for primary pterygium by ophthalmology trainees - Kositphipat K. (2017)
© 2016, Springer Science+Business Media Dordrecht. To evaluate the results of pterygium excision with conjunctival autograft transplantation for primary pterygium performed by trainee ophthalmologists. Design Prospective interventional case series. Setting A tertiary eye care center in northern Thailand. Participants Patients with primary pterygium recruited from July 2011 to August 2012. Intervention In all cases, the affected eye underwent pterygium excision followed by a superior conjunctival autograft carried out by trainee ophthalmologists. Main outcome measure The recurrence of pterygium and other post-operative complications. Results Sixty-two eyes from 54 patients were studied. There were 36 females (66.7 %) and 18 males (33.3 %). The mean age of the patients was 54.5 (±9.8) years with the mean corneal invasion measured at 3.3(±0.8) mm. Pterygium morphologies of Grade 1, Grade 2, and Grade 3 were 33.9, 48.4, and 17.7 %, respectively, with the mean follow-up time of 17.3 (±7.9) months. Pterygium recurred in the cornea of six eyes (9.7 %). All recurrences occurred within 6-month post-operation. Other post-operative complications included conjunctival recurrence (4.8 %), graft retraction (3.2 %), conjunctival cyst (3.2 %), and increased intraocular pressure (1.6 %). The recurrence of pterygium was not associated with the patient age (p = 0.72), occupation (p = 0.23), sun exposure time (p = 0.18), pterygium duration (p = 0.22), pterygium size (p = 0.67), or pterygium morphology (p = 0.85). Conclusion The recurrence rate and post-operative complications of pterygium excision with conjunctival autograft performed by trainee ophthalmologists were within acceptable limits. All recurrence occurred within 6 months after surgery.